Detection of inherited chromosomally integrated HHV‐6 (ciHHV‐6) in a marker chromosome. (31st March 2017) - Campioni, Diana; Gentili, Valentina; Cavazzini, Francesco; Bortolotti, Daria; Nacheva, Elisabeth P.; Cuneo, Antonio; Di Luca, Dario; Rizzo, Roberta
Abstract: Objectives: Inherited chromosomally integrated human herpesvirus‐6 (ciHHV‐6) is characterised by the complete HHV‐6 genome integration into the host germ line genome and is vertically transmitted with a Mendelian inheritance. By now, the only relationship between ciHHV‐6 and diseases seems to be with angina pectoris. Methods: We report a case of an 82‐year‐old man diagnosed with diffuse large B‐cell lymphoma (DLBCL) on October 2014. To substantiate the suspicion of ciHHV‐6, we analysed peripheral blood mononuclear cells, bone marrow biopsy and pleural effusion‐derived mesothelial cells with PCR, RT‐PCR and FISH. Results: Virological routine screening by PCR showed the absence of HHV‐8 and EBV infections, while the presence of HHV‐6 DNA (ie, U22, U42 and U94 HHV‐6 genes), with a viral load of about 1.0 genome per cell, strongly suggests ciHHV‐6. The RT‐PCR showed the positivity only for the immediate‐early U94, at low levels of transcription (100±15 transcripts/1 μg RNA). FISH analysis reported a case of inherited ciHHV‐6 in 17p chromosome region and, for the first time, in a marker chromosome. Conclusions: This is the first case of inherited ciHHV‐6 in a marker chromosome, possibly elucidating the role of this abnormality in the biology of DLBCL.